Quarternary Sediment Characteristics of Floodplain area: Study Case at Kampar River, Rumbio Area and Surroundings, Riau Province - Yuniarti Yuskar; Dewandra Bagus Eka Putra; Muhammad Revanda (UIR PRESS, 2018)
The study area is located in some floodplains of meandering river environment along the Kampar River, Rumbio. Typical morphology of meandering river that found in this area can be classified as stream channel, floodplain, abandoned channel, and sand bars deposit. Meandering river system carries sediment supply by suspended and bed - load (mixed load) in conjunction with low energy into a particular characteristic on sediment deposition. This study aims to determine the characteristics of the sediments, changes in vertical and lateral spread of sediment deposition on the floodplain environment. This study conducted by field survey using a hand auger of 1.5m - 4m depth and trenching which is a layer that has been exposed of 1-2 meters depth. Further analysis had been carried out using granulometri method and core data analysis to determine the characteristics and depositional facies. Sediment deposit that formed along the Kampar River is the result of the main channel migration of Kampar River. The characteristic of quaternary sediment facies is coarse to gravelly sand on the bottom followed by fine to very fine sand with pattern fining upwards and silt to clay and abundant terrestrial organic matter at the uppermost layer. Depositional facies are determined based on the characteristics of sediment facies which can be grouped into a stream channel, oblique accretion deposits, sand bars and overbank deposits.